DETERMINATION OF PHYSICAL AND MECHANICAL PROPERTIES OF POLYETHYLENE AND POLYMER NANOCOMPOSITES USING THE METHODS OF MOLECULAR DYNAMICS - OMELCHUK, IRYNA; KARVATSKII, ANTON (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Today, molecular dynamics (MD) simulation become an effective method for investigating and predicting the physical and mechanical properties (PMP) of materials at the atomic scale. In this work, initial configurations of molecular systems of pure polyethylene (PE) and carbon nanotube-reinforced nanocomposites (PE-CNT) are created and described by the united atom model and Dreiding force field. Equilibration of the initial configurations of molecular models carried out using NVT and NPT ensembles in LAMMPS. Simulated complex of PMP of PE and PE-CNT includes elastic modulus, Poisson’s ratio, bulk modulus, shear modulus, yield strength, mass isobaric heat capacity, and coefficient of linear thermal expansion (CLTE). The results verification of the PE molecular model showed the obtained MD simulation data either coincide with available literature data or are close to them. The results justify the use of the same algorithms to obtaine reliable data on the PMP of PE-CNT. Comparing the complex PMP of molecular models of pure PE and PE-CNT, it was established the elastic modulus of PE-CNT α=1.4 % increases by 10.4% at 300 K and by 29.3% at 320 K. The yield strength of PE-CNT α=1.4 % also increases by 33.2 % at a strain rate of 109 s−1 and a temperature of 300 K compared to PE. Meanwhile, mass isobaric heat capacity and CLTE decrease with increasing temperature: mass isobaric heat capacity decreases by 1.3 % at 300 K and by 4.4 % at 320 K; CLTE decreases by 20.2 % at 300 K and by 22.6 % at 320 K. Nonlinear two-parameter dependencies of the PMP of PE-CNT obtained in the temperature range (280–320) K and the volume fraction of fillers (0–1.5) %. These results allow to develop of new composite materials without conducting sufficiently complex and time-consuming numerical experiments based on MD simulation. The obtained data on the complex PMP are necessary for modeling the thermo-elastic-plastic state of products made of PE-CNT under operational conditions in a continuum approximation.